THE INNOVATION OF ISLAMIC INSURANCE AS A SOLUTION FOR PENETRATION - Nurul Azizah Azzochrah; Rosdalina Bukido; Sofyan Octavian Tubagus (IAIN Manado, 2021)
The penetration of Islamic insurance in Indonesia is not directly proportional to the number of Muslim population in Indonesia. This article aims to look at the causes of the low penetration of Islamic insurance in Indonesia. Literature study is the method used in this article by conducting content analysis, the data used in the form of writing, graphics, pictures and figures sourced from the OJK and the ASEAN Economic survey. The result of this research is the lack of innovation in Islamic insurance which caused the low penetration of Islamic insurance. Islamic insurance penetration can increase with innovation. Social insurance is a manifestation of the mandate of 1945 Constitution of Indonesia Republic which obliges to provide basic protection for all Indonesian people. With the large number of Muslim population in Indonesia, the opportunities for Sharia social insurance innovation can be taken into consideration. Sharia social insurance can be a solution to increasing the penetration of Sharia social insurance in Indonesia. In terms of regulation, the growth of Sharia social insurance can develop. This article has major implications for practitioners, policy makers and regulators.